-8.75x+14=-5.25x+-3.5

Simple and best practice solution for -8.75x+14=-5.25x+-3.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8.75x+14=-5.25x+-3.5 equation:



-8.75x+14=-5.25x+-3.5
We move all terms to the left:
-8.75x+14-(-5.25x+-3.5)=0
We add all the numbers together, and all the variables
-8.75x-(-5.25x-3.5)+14=0
We get rid of parentheses
-8.75x+5.25x+3.5+14=0
We add all the numbers together, and all the variables
-3.5x+17.5=0
We move all terms containing x to the left, all other terms to the right
-3.5x=-17.5
x=-17.5/-3.5
x=+5

See similar equations:

| -5s=−13 | | 12=-n-2 | | 175m-100m+48000=50750-175m | | 12.5x+30=(-7.5x)+90.5 | | -8x-2=5x+7 | | 3(b+2)-4(b-3)=5b | | 4x-2(1-x)=-32 | | -3(15g-5)=5(-12-12g) | | 2x+3=9*5 | | -2(v+6)+6v=4 | | 2x+0.5x=430000 | | 3a-8=118 | | 2.5x-1.4=6.1 | | -2x+7=5-4x+1 | | 4r+9=77 | | 5(n+1)=7(n-3) | | 4(x-6)+2x=-24+6x | | 53x−4+23x+10=9 | | (3x+7)+(9x-43)=189 | | y^2-((y^2)/4)-(4/(y^2))-2=0 | | 8x+5=5-2x | | -3=v-10 | | -2(3x+9)=2(-3x+9) | | 2+v/2=5 | | 16x=1/64x= | | f(7)=26 | | 2r+5/3+6=19 | | 10x-14-12x+3=-23 | | -7x-8=5x+8(8x-1) | | -2(x+3)=x-9+3(4x+3) | | 3x-10=9x+12 | | f(7)=27 |

Equations solver categories